2009
DOI: 10.1038/npp.2009.164
|View full text |Cite
|
Sign up to set email alerts
|

Early Response to Antipsychotic Drug Therapy as a Clinical Marker of Subsequent Response in the Treatment of Schizophrenia

Abstract: Our objective was to prospectively assess whether early (ie, 2 weeks) response to an antipsychotic predicts later (12-week) response and whether 'switching' early non-responders to another antipsychotic is a better strategy than 'staying'. This randomized, double-blind, flexible-dosed, 12-week study enrolled 628 patients diagnosed with schizophrenia or schizoaffective disorder. All initiated treatment with risperidone. Early response was defined as X20% improvement on the Positive and Negative Syndrome Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(183 citation statements)
references
References 38 publications
9
169
1
4
Order By: Relevance
“…The outcome of the switchers was slightly, but statistically significantly (P = .02) better than that of the stayers, and the difference was more pronounced in patients who were at least moderately ill at week 2. 30 In any case the early improvers at 2 weeks had a clearly better outcome than the early nonimprovers, irrespectively of the subsequently assigned treatment of the latter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of the switchers was slightly, but statistically significantly (P = .02) better than that of the stayers, and the difference was more pronounced in patients who were at least moderately ill at week 2. 30 In any case the early improvers at 2 weeks had a clearly better outcome than the early nonimprovers, irrespectively of the subsequently assigned treatment of the latter.…”
Section: Resultsmentioning
confidence: 99%
“…Strongest support that switching nonresponders to a different drug is effective, stems from a recent large trial in which 628 mainly chronic patients with schizophrenia or schizoaffective disorder were treated for 2 weeks with flexibly dosed risperidone (2-6 mg/d, Kinon et al 30 ). Those who had not shown at least a 20% reduction of the PANSS were randomized to double-blind treatment with either continuation of risperidone or a switch to olanzapine (10-20 mg/d) for an additional 10 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the last years it was repeatedly demonstrated that early antipsychotic response is a strong predictor of subsequent response [14][15][16][17][18][19][20][21]. We therefore hypothesized that ER patients could represent a distinct subgroup of patients, identified by specific clinical and demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…According to the "early onset hypothesis" of antipsychotic action, an increasing number of studies showed that the early response to antipsychotics is a very robust predictor of longterm outcome [14][15][16][17][18][19][20][21]. Early response is defined in different manners by different Authors.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic efficacy appears to be tied -at least to some extent -to dopamine (D 2 ) blockade. Recent enthusiasm that glutamate alone might be a distinct target has been dampened by the results of a recent trial of a glutamatergic drug that had shown initial promise [10] . Additionally, these drugs have highly variable pharmacologic profiles at several other neuroreceptors.…”
Section: Pharmacotherapy Of Schizophrenia: Contextual Issues For Pharmentioning
confidence: 99%